2020
DOI: 10.1159/000505213
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferase P1 Polymorphism on Exon 6 and Risk of Hepatocellular Carcinoma in Thai Male Patients

Abstract: <b><i>Introduction:</i></b> Hepatocellular carcinoma (HCC) is the fifth most common malignancy and the fourth leading cause of cancer-related deaths worldwide. HCC cases are two to four times more common in males than in females, and the highest incidence is found in Asia and Sub-Saharan Africa. This gender disparity is the result of different behavioral risk factors, such as smoking and drinking alcohol. Glutathione S-Transferase P1 (GSTP1) is an enzyme that is involved in the detoxifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This gender disparity is the result of different behavioral risk factors, such as smoking and drinking alcohol. Glutathione S‐Transferase P1 (GSTP1) exon 6 polymorphism genotype was associated with an increase in the risk of HCC in male patients …”
Section: Gender Race and Ethnicitymentioning
confidence: 99%
“…This gender disparity is the result of different behavioral risk factors, such as smoking and drinking alcohol. Glutathione S‐Transferase P1 (GSTP1) exon 6 polymorphism genotype was associated with an increase in the risk of HCC in male patients …”
Section: Gender Race and Ethnicitymentioning
confidence: 99%
“…Kudhair [26] analyzed in Arab populations and revealed that carrying GSTP1 Ile105Val substitution is positively correlated with a higher risk for lung cancer in WP tobacco smokers. Conversely, Sophonnithiprasert [27] reported for the insigni cant difference between GSTP1 Ile105Val polymorphism and oxaliplatin-induced toxicity. Our research showed GSTP1 c. 313A>G polymorphism was linked to acute toxicity in colorectal cancer patients undergoing neutropenia and ulceration.…”
Section: Discussionmentioning
confidence: 96%
“…Kudhair [32] analyzed Arab populations and revealed that carrying GSTP1 Ile105Val substitution is positively correlated with a higher risk for lung cancer in WP tobacco smokers. Conversely, Sophonnithiprasert [33] reported an insigni cant difference between GSTP1 Ile105Val polymorphism and oxaliplatin-induced toxicity. Our research showed GSTP1 c. 313A>G polymorphism was linked to acute toxicity in colorectal cancer patients undergoing skin ulceration, which con icting with research from Terrazzino [34] and Osti [35].…”
Section: Discussionmentioning
confidence: 96%